Description of the Aegean and other islands a facsimile of the manuscript at the James Ford Bell Library, University of Minnesota - Christophorus de Bondelmontibus 1385-1431; Martellus Germanus, Henricus (Italica Press, 2018)
"A facsimile, transcription and translation of the James Ford Bell Library (University of Minnesota) manuscript of Cristoforo Buondelmonti's "Descriptio Arcipelagi Et Cicladum Aliarumque Insularum" copied by Henricus Martellus Germanus"...
Includes bibliographical references and index
Keywords: Buondelmonti, Cristoforo -- approximately 1385-approximately 1430 -- Travel -- Aegean Islands (Greece and Turkey); Geschichte 1400-1475; Geografie; Aegean Islands (Greece and Turkey) -- Description and travel -- Early works to 1800; Aegean Sea Region -- Description and travel -- Early works to 1800; Aegean Islands (Greece and Turkey) -- History -- Sources; Aegean Sea Region -- History -- Sources; Griechenland; Ägäische Inseln; Britannien; Zypern; Sizilien; Sardinien; Korsika; Atlas; Quelle